Student food selection behaviour after returning to face-to-face classes - Huaman-Romani, Yersi-Luis; Garrido-Arismendis, Juan-Jesús; Agurto-Zapata, Jhon-Felix; Juarez-Vera, Nayely-Paola; Hinojosa-Benavides, Rene-Antonio (International Journal of Innovative Research and Scientific Studies, 2023)
The pandemic raised awareness about the consumption of healthy and high- quality food which was practiced at home leaving aside the consumption of "junk food" but students are returning to the consumption of these unhealthy foods in university. The objective of this research is to describe and analyze the behavior of students in the selection of their food (good and bad for health) after returning to school. The methodology applied is descriptive, correlational and predictive of a cross-sectional quantitative type in which 765 students participated anonymously and voluntarily in an online survey. Results. A low level of consumption of "good" foods was found while the consumption of "bad" foods is growing daily. Conclusion. " Good" food is only eaten at home while “bad" food is eaten everywhere A policy of selling healthy food should be implemented. If these foods are not regulated, there is a tendency to have an overweight university student population in the future.